topicalisation as distinct from left-dislocation: evidence from modern literary arabic - abdel-majid ibrahim thalji (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
topicalisation as distinct from left-dislocation: evidence from modern literary arabic